PENGARUH REKRUTMEN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT DOK DAN PERKAPALAN KODJA BAHARI JAKARTA UTARA - Listiani, Tini; Effendy , Aidil Amin (Journal of Research and Publication Innovation, 2024)
This study aims to examine the effect of Recruitment and Compensation on employee performance partially and simultaneously at PT Dok and Perkapalan Kodja Bahari in North Jakarta. This research method uses a quantitative associative approach description method, using 153 respondents. The sampling method used in this study was to use a random sampling technique by calculating 153 populations using the slovin formula so that a sample of 110 respondents was obtained. Data analysis processing techniques used descriptive analysis, classic assumption test, regression test, correlation test, coefficient of determination test, and hypothesis testing. Recruitment and compensation have a simultaneous effect on employee performance with the regression equation Y = 28,511 + 0.154 X1 + 0.223 X2. The correlation coefficient value obtained is 0.413, meaning that the independent variable and the dependent variable have a moderate level of influence with a coefficient of determination or simultaneous influence of 15.5% while the remaining 84.5% is influenced by other factors. Hypothesis testing obtained F count > F table or ((11.029 > 2.690), this is also reinforced by a significance probability of 0.045 <0.05. Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant effect between Recruitment and Compensation on Performance employees of PT Dok and Shipping Kodja Bahari in North Jakarta.